ANALISIS PENGARUH PERANG, KEMISKINAN DAN DISKRIMINASI TERHADAP PEREMPUAN DAN ANAK DALAM KONTEKS PERDAGANGAN MANUSIA - Yusnarida Eka Nizmi (UIN ALAUDDIN MAKASSAR, 2020)
This study aims to describe the unhappiness of being women and children since human trafficking crimes dissapear their lives that driven by war, poverty and discrimination. There are various casualities that trigger human trafficking and the involvement of trafficker in this humanity crime. This study reviews various literatures since library research is the method of this research. This research analyzes the concept of war, poverty, and domestic conflict. Women and children become vulnerable target to be smuggled illegally to destination countries. Many of them finally end up in torture, violance and sexual exploitation. They have to keep working with minimum salary just for paying transportation cost. For smugglers, these vulnerable people are potential target to get money from selling them to other person or group. The smugglers lied to them about the truly motives and for the victims, the cost and exploitation are the consequences to reveal all their the horrible conditions. This research shows that how women and children start their sad journey since devastated and insecure in the neighbourhood because of war, domestic conflict and never ending poverty